The effect of L-carnitine supplementation on lipid profile in adults: an umbrella meta-analysis on interventional meta-analyses - Musazadeh, Vali; Alinejad, Hanie; Esfahani, Niloofar Kouhi; Kavyani, Zeynab; Keramati, Majid; Roshanravan, Neda; Mosharkesh, Erfan; Dehghan, Parvin (Frontiers in Nutrition, 2023)
Introduction: Previous meta-analyses investigating the therapeutic effects of L-carnitine on lipid profiles have demonstrated inconsistent results. The present umbrella meta-analysis aimed to investigate the impact of efficacy of L-carnitine on lipid profiles in adults.Methods: Databases including PubMed, Scopus, and Embase, Web of Science, and Google Scholar were searched up to June 2023. Meta-analysis was performed using a random-effects model.Our results from thirteen meta-analyses indicated that L-carnitine supplementation significantly total cholesterol (TC) (ES= -1.05 mg/dl, 95% CI: -1.71, -0.39; p= 0.002), triglycerides (TG) (ES = -2.51 mg/dl; 95% CI: -3.62, -1.39, p <0.001), and low-density lipoprotein-cholesterol (LDL-C) (ES= -4.81 mg/dl; 95% CI: -6.04, -3.59; p<0.001). It also increased high-density lipoprotein-cholesterol (HDL-C) (ES: 0.66 mg/dl, 95% CI: 0.20, 1.12, p=0.005) levels.The present umbrella meta-analysis suggests supplementation with L-carnitine in a dosage of more than 2 g/day can improve lipid profile. Thus, L-carnitine supplementation can be recommended as an adjuvant anti-hyperlipidemic agent.